THREAT ANALYSIS OF THE REGIONAL TERRORISM FINANCING - Isnanto, Samto Hadi; Praditya, Yosua (Indonesia Defense University, 2016)
The terrorism financing threats is a prominent issue in South East Asia region that must be tackled by Indonesian government in mitigating the development of Islamist radical group. In order to maintain the operational and financial group, then the vast funds is very needed which obtainable by several means. Fund gathering, fund movement, and fund allocation are those activities usually conducted by the group, and this does not make terrorist would stop in varying some ways to increase their fund. The fund plays a vital role to the groupâ€™s existence due to operational cost, particularly in recruiting, hiring, and indoctrinating new members. The influx of money could be sourced from inside and outside country. When one speaks of terrorism funding, it could not be separated from the donor, movement and usage, which also covered as legal entity, banks, NGOs and individual donations. All these actors must be faced through policy and legal means which connecting with specific stakeholders, particularly those who advance in banking system.Â Kata Kunci: terrorism financing, security